2010
DOI: 10.3109/1354750x.2010.520336
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of two enzyme systems inEuchlanis dilatata(Rotifera: Monogononta) as biomarker of effect of metals and pesticides

Abstract: The inhibitory effects on esterases and phospholipase A2 (PLA2) in the freshwater rotifer Euchlanis dilatata, native to Mexico, were assessed by fluorimetry after in vivo exposure (30 min) in laboratory conditions to sublethal concentrations of metals and pesticides. EC(50) values for esterases ranged from 7.9 × 10(-7) for DDT to 61.9 μg l(-1) for methyl parathion, while corresponding values for PLA2 ranged from 0.96 × 10(-6) for mercury to 69.2 μg l(-1) for lead. These enzyme systems in E. dilatata are very s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…In invertebrates, it generates oxidative stress and time-and dose-dependent deregulation of transcription. For example, it up-regulates the expression of antioxidant enzymes [4], metallothioneins (MTs) and heat shock proteins (HSPs) [5], whereas it downregulates the expression of digestive enzymes [6], esterases and phospholipase A2 [7]. Cadmium also interferes with immune responses [8,9], tissue organization and histology [10,11], and cell cycles by inducing apoptosis [12].…”
Section: Introductionmentioning
confidence: 99%
“…In invertebrates, it generates oxidative stress and time-and dose-dependent deregulation of transcription. For example, it up-regulates the expression of antioxidant enzymes [4], metallothioneins (MTs) and heat shock proteins (HSPs) [5], whereas it downregulates the expression of digestive enzymes [6], esterases and phospholipase A2 [7]. Cadmium also interferes with immune responses [8,9], tissue organization and histology [10,11], and cell cycles by inducing apoptosis [12].…”
Section: Introductionmentioning
confidence: 99%
“…In the rotifer E. dilatata (FW), a native species from Mexico, the inhibition of esterases and phospholipase A2 was assessed fluorometrically after in vivo exposure (30 min) to sublethal concentra-tions of metals and pesticides in laboratory conditions. This study concluded that both enzymes are very sensitive to toxicants-induced alterations [96,97].…”
Section: Perspectives For Future Studies Regarding the Importance Of mentioning
confidence: 65%
“…In the case of methyl parathion, which shows higher acute toxicity, a range from 0.607 mg/L for Euchlanis dilatata to 29.19 mg/L for B. calyciflorus was found. Another organophosphorus of ecotoxicological relevance, chlorpyrifos, tends to affect significantly aquatic invertebrates due the LC50 values reported for B. koreanus (3.9 mg/L) and B. calyciflorus (11.85 mg/L) [96,134,136,137].…”
Section: Rotifer Sensitivitymentioning
confidence: 99%
“…Other new indicator organisms proposed for use in freshwater toxicity bioassays included Ceriodaphnia cornuta (Lopes et al, 2011), the rotifer Euchlanis dilatata (Arias-Almeida and Rico-Martinez, 2011a;, predatory aquatic beetles (Burghelea et al, 2011),…”
Section: Developmental Effects and Genotoxicity Inmentioning
confidence: 99%